Peran Komite Sekolah Di Sekolah Menengah Atas - Helmi Hidayanti; Sumarlin Mus; Irmawati Irmawati (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2023)
This study examines the role of school committees in high schools. The purpose of this study was to determine the role of school committees in high schools. The approach used in this study is a qualitative approach with a descriptive type of research. The sources of data in this study were school committee chairmen, principals, and teachers. Data collection techniques include interviews, observations, and documentation. Data analysis using the Miles and Huberman model. Data validity check using triangulation. The results showed that the role of the school committee in Senior High School is 1) As an advisory agency for fundraising programs and also provides policies for underprivileged students exempt from school committee payments; 2) As a supporting agency by collecting budget for additional salaries of honor teachers, honor administrative staff, and cleaning services as well as to facilitate extracurricular activities; 3) As the controlling agency evaluates the fundraising program for additional salaries of honor teachers, honor administrative staff, and cleaning services, the school committee also supervises budget managers; 4) As a mediator the school committee accommodates the aspirations, ideas and ideas submitted by parents for the progress of the school.